Thermally Induced Irreversible Disorder in Interlayer Stacking of γ-GeSe - Kim, Joonho; Lee, Giyeok; Lee, Sol; Park, Jinsub; Lee, Kihyun; Jung, Joong Eon; Lim, Seungjae; Jang, Jeongsu; Bae, Heesun; Lee, Jae Ung; Im, Seongil; Soon, Aloysius; et al. (Small, 2024)
The interlayer stacking shift in van der Waals (vdW) crystals represents an important degree of freedom to control various material properties, including magnetism, ferroelectricity, and electrical properties. On the other hand, the structural phase transitions driven by interlayer sliding in vdW crystals often exhibit thickness-dependent, sample-specific behaviors with significant hysteresis, complicating a clear understanding of their intrinsic nature. Here, the stacking configuration of the recently identified vdW crystal, γ-GeSe, is investigated, and the disordering manipulation of stacking sequence is demonstrated. It is observed that the well-ordered AB′ stacking configuration in as-synthesized samples undergoes irreversible disordering upon Joule heating via electrical biasing or thermal treatment, as confirmed by atomic resolution scanning transmission electron microscopy (STEM). Statistical analysis of STEM data reveal the emergence of stacking disorder, with samples subjected to high electrical bias reaching the maximum levels of disorder. The energies of various stacking configurations and energy barriers for interlayer sliding are examined using first-principles calculation and a parameterized model to elucidate the key structural parameters related to stacking shift. The susceptibility of interlayer stacking to disorder through electrical or thermal treatments should be carefully considered to fully comprehend the structural and electrical properties of vdW crystals.
Keywords: Atomic resolution transmission electron microscopy; Atomic-resolution; First principle calculations; Interlayer sliding; Interlayer stacking; Joules heating; Stacking disorders; Transmission electron; Van der Waal; Γ-gese; atomic resolution transmission electron microscopy; first-principles calculation; interlayer sliding; Joule heating; stacking disorder; γ-GeSe